2019
DOI: 10.1177/1098214019860912
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Evaluation’s Presence in the Undergraduate Curriculum in the United States

Abstract: Evaluator education programs have developed to help support the growth of professional evaluators and improve evaluation practice. Empirical research has described where and how evaluation is taught at the graduate level of education, but little is known about the undergraduate level. This study empirically explores how, if at all, evaluation is taught at the undergraduate level by systematically analyzing the publicly available curricula of the top 40 public and top 40 private universities in the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Collectively, these studies focus exclusively on describing the content and emphasis of topics or competencies in university-based programs (Christie et al, 2014; Davies & McKay, 2014; J. D. Dewey et al, 2008; Fierro & Christie, 2011; Galport & Azzam, 2016; LaVelle, 2020; LaVelle et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Collectively, these studies focus exclusively on describing the content and emphasis of topics or competencies in university-based programs (Christie et al, 2014; Davies & McKay, 2014; J. D. Dewey et al, 2008; Fierro & Christie, 2011; Galport & Azzam, 2016; LaVelle, 2020; LaVelle et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…It is further anticipated that the outcome of this research will offer evidence-based findings to help inform university executive strategic decision-making. The benchmarking scan and literature review are precedented methods used to understand the evaluation landscape (Hunter & McDavid, 2019; King & Ayoo, 2020; LaVelle, 2019; LaVelle et al, 2019). This contributes to the field of education by encouraging debate around evaluation education.…”
Section: Methodsmentioning
confidence: 99%
“…Courses were first categorized as either evaluation or inquiry, wherein an evaluation course included the term “evaluation” in the course title and then coded based on the scope of evaluation content covered (e.g., evaluation as a topic) and level of practice (e.g., micro, mezzo, or macro). For consistency, we used identical inclusion criteria as LaVelle et al (2019) wherein evaluation-specific courses included traditional evaluation activities such as engaging stakeholders, program/intervention analysis, evaluation design, data collection and analysis, and report writing, all with a focus on decision making or valuing judgments. Courses were considered evaluation-related if they treated evaluation as a topic within a larger course (e.g., grant writing or organizational development).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Morris (1994) argued extensively about the value of single-course experiences in evaluation that could help develop evaluation users if not evaluation practitioners. Later, LaVelle et al (2019) developed a methodology to look at where and how evaluation is taught to undergraduate students in the top 50 public and top private colleges and universities in the United States. Their study suggested that undergraduate students had broader exposure to evaluation than previously thought, even though much of the exposure positioned evaluation as a subtopic within a much larger course such as industrial/organizational psychology, environmental sciences, and education.…”
Section: Evaluator Education Over Timementioning
confidence: 99%